The effectiveness of a training program based on the speech therapy method in reducing the severity of stuttering among a sample of fourth-grade students in basic education in public schools in Damascus Governorate (Damascus University Journal of educational and Psychologyical sciences, 2024)
The research aimed to determine the effectiveness of a training program based on a speech therapy method in reducing the severity of stuttering among a sample of fourth-grade students in basic education in public schools in Damascus Governorate. The research sample consisted of (24) male and female students who stutter, who were randomly distributed into two equal groups (experimental and control), each of which included (12) male and female students, (9) males and (3) females. Using the following tools (a monitoring list for indicators of the presence of stuttering disorder in students, a measure of stuttering severity, the Raven’s Progressive Matrices Test (1998), and a training program based on the speech therapy method). I reached the following results:1- There are statistically significant differences at the significance level (0.05) between the average ranks of the scores of the experimental group members and the average ranks of the scores of the control group members in the direct post-measurement on the stuttering severity scale, in favor of the experimental group members.2-There are statistically significant differences at the significance level (0.05) between the average ranks of the experimental group members’ scores in the direct pre- and post-measurements on the stuttering severity scale in favor of the direct post-measurement.3- There are statistically significant differences at the significance level (0.05) between the average ranks of the experimental group members’ scores in the direct post-measures and the deferred post-measures on the stuttering severity scale in favor of the deferred post-measurement.
Keywords: Stuttering; Basic Education; Speech Therapy Style